Search for pair-produced scalar and vector leptoquarks decaying into third-generation quarks and first- or second-generation leptons in pp collisions with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Exotics, Hadron-Hadron Scattering.; Springer Open.